A method for preserving large-scale flow patterns in low-resolution ocean simulations. (May 2021) - Shevchenko, I.; Berloff, P.
Abstract: It is typical for low-resolution simulations of the ocean to miss not only small- but also large-scale patterns of the flow dynamics compared with their high-resolution analogues. It is usually attributed to the inability of coarse-grid models to properly reproduce the effects of the unresolved small-scale dynamics on the resolved large scales. In part, the reason for that is that coarse-grid models fail to at least keep the coarse-grid solution within the region of phase space occupied by the true solution (the high-resolution solution projected onto the coarse grid). In this paper we offer a solution to this problem by computing the image point in the phase space restricted to the region of the true flow dynamics. The proposed method shows encouraging results for both low- and high-dimensional phase spaces, it takes a near-zero effort to implement into existing numerical codes and has ample room for further improvements. Highlights: A method for preserving large-scale patterns in low-resolution models is proposed. The method has been significantly improved by using nudging methodology. The method with and without nudging has been tested on the Lorenz 63 and QG model. Results show the method without nudging fails to preserve large-scale flow patterns. Results show the method with nudging preserves large-scale flow patterns.